The effect of teaching metacognitive strategies on students’ metacognitive awareness and academic performance of students - Abed Noori (Development Strategies in Medical Education, 2016)
Introduction: Studies show that metacognitive awareness is necessary for students’ academic achievement. Some factors affect the development of this awareness. The aim of this study is to assess the effect of teaching metacognitive strategies on metacognitive awareness and academic performance of students of Al Boye Gorgan Nursing School.